Impact of next‐generation sequencing panels in the evaluation of limb‐girdle muscular dystrophies. (7th May 2019) - Özyilmaz, Berk; Kirbiyik, Özgür; Özdemir, Taha R.; Kaya Özer, Özge; Kutbay, Yaşar B.; Erdogan, Kadri M.; Güvenç, Merve Saka; Kale, Murat Yildirim; Gazeteci, Hande; Kiliç, Betül; Sertpoyraz, Filiz; Diniz, Gulden; et al.
Abstract: Introduction: Limb‐girdle muscular dystrophy (LGMD) is the fourth most common muscular dystrophy, with progressive proximal muscle weakness. However, a large number of neuromuscular conditions are similarly presented. Because of this, the use of high‐throughput methods such as next‐generation sequencing (NGS) is important in the evaluation of LGMD. Methods: In this report, we applied a custom target capture‐based NGS panel covering 31 LGMD‐associated genes ( MYOT, LMNA, CAV3, DES, DNAJB6, FLNC, CAPN3, DYSF, SGCG, SGCA, SGCB, SGCD, TCAP, TRIM32, FRKP, TTN, POMT1, ANO5, FKTN, POMT2, POMGnT1, DAG1, PLEC, GAA, GMPPB, HNRNPDL, TNPO3, LIMS2, POMK, TRAPPC11, ISPD ) in 74 patients suspected of LGMD. Results: In 25 (33.8%) out of 74 patients analyzed, one or more pathogenic/likely pathogenic variants in 13 different genes were detected. Six of the patients had the variants that were not found in databases and literature; thus, they were interpreted as novel pathogenic variants. Discussion: The diagnosis rate achieved (33.8%) is consistent with previous literature reports and underlines the efficiency and importance of NGS technology in the molecular genetic evaluation of LGMD.